2015
DOI: 10.1007/s10522-015-9604-x
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle cells possess a ‘memory’ of acute early life TNF-α exposure: role of epigenetic adaptation

Abstract: Sufficient quantity and quality of skeletal muscle is required to maintain lifespan and healthspan into older age. The concept of skeletal muscle programming or memory has been suggested to contribute to accelerated muscle decline in the elderly in association with early life stress such as fetal malnutrition. Further, muscle cells in vitro appear to remember the in vivo environments from which they are derived (e.g. cancer, obesity, type II diabetes, physical inactivity and nutrient restriction). Tumour-necro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 57 publications
0
58
0
Order By: Relevance
“…Earlier studies reported that high-fat diet increases [70] and CR reduces TNFα expression in SM [71], suggesting that CR may circumvent the apoptotic effect of TNFα in SM [72]. Acute early life exposures to TNFα renders muscle cells more susceptible to impaired regeneration when inflammation is encountered in later proliferative life [73], which supports the role TNFα in muscle degeneration. Interestingly, the TNFRSF12A gene was significantly upregulated by WSD and downregulated by CR (Additional file 2: Table S1 and Table 2), while the transcriptional activation of this gene has been previously linked to diffuse muscle atrophy [74].…”
Section: Discussionmentioning
confidence: 70%
“…Earlier studies reported that high-fat diet increases [70] and CR reduces TNFα expression in SM [71], suggesting that CR may circumvent the apoptotic effect of TNFα in SM [72]. Acute early life exposures to TNFα renders muscle cells more susceptible to impaired regeneration when inflammation is encountered in later proliferative life [73], which supports the role TNFα in muscle degeneration. Interestingly, the TNFRSF12A gene was significantly upregulated by WSD and downregulated by CR (Additional file 2: Table S1 and Table 2), while the transcriptional activation of this gene has been previously linked to diffuse muscle atrophy [74].…”
Section: Discussionmentioning
confidence: 70%
“…HRM-PCR for total DNA methylation HRM-PCR for CpG methylation was performed as previously described (24). In brief, 20 ng DNA was subjected to HRM-PCR using EpiTect HRM-PCR kits and Rotorgene 3000Q (Qiagen) with Rotorgene software.…”
Section: Dna Methylation By Pcr and Pyrosequencingmentioning
confidence: 99%
“…This relationship was subsequently used to quantify the percentage methylation from the integrated raw melt curves of the experimental samples. Calculations were performed by using a Python-based program, MethylCal, that was developed for this purpose in-house [used previously (24)].…”
Section: Dna Methylation By Pcr and Pyrosequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…A general trend towards reduced promoter methylation levels of genes involved in energy metabolism, myogenesis, contractile activity, and oxidative stress resistance became apparent when global methylation patterns in skeletal muscle of healthy aged men with a lifelong history of physical activity were compared to “couch potatoes” of the same age group (Sailani et al, 2019). Reciprocally, also “bad memories” inflicted by physical inactivity, unhealthy diet, and prenatal stress have been reported to become reflected by differential DNA methylation patterns in skeletal muscle tissue (Alibegovic et al, 2009; Jacobsen et al, 2012; Jacobsen et al, 2014; Nilsson & Ling, 2017; Nitert et al, 2012; Sharples, Polydorou et al, 2016; Sheppard et al, 2017).…”
Section: Skeletal Muscle Exercise and Flexible Epigenomementioning
confidence: 99%